Supply Chain Measuring Performance with Scor Model Business Process Mapping - Wahyudi Wahyudi; Haliah Haliah; Andi Kusumawati (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This study provides a general framework for measuring general supply performance. This research uses business process mapping with the Supply Chain Operations Reference (SCOR) model. Data collection methods by interviews, observations, document inspections, and literature studies. The findings of this study show that the business processes of PT Semen Bosowa Maros have been implemented well. Of the 12 performance measurement metrics used, there are 8 metrics with details, namely: internal meeting, planning cycle time, source defect rate, source fill rate, failure in the process, orders ready to pick by a customer, customer complaint, and return rate has been in an excellent position (excellent). Three other metrics have been in a good position: source lead time, machine efficiency, and delivery fill rate. Only the forecast accuracy metric is in a marginal position